Analisis Faktor-Faktor Pembentuk Manajemen Komunikasi Pada Generasi Z - Tri Rumayanto; Siti Nurjannah; Sri Sutali Bani (Jurnal Ilmiah Ilmu Manajemen, 2026)
The development of digital technology has transformed communication patterns in society, particularly among Generation Z, digital natives who use digital media as their primary means of interaction. This study aims to comprehensively analyze the factors shaping communication management among Generation Z, encompassing technological, psychological, social, and ethical aspects of communication. The study employed a descriptive qualitative approach with a literature review method, and was analyzed using the Miles and Huberman interactive model. The results indicate that digital technology is a dominant factor shaping fast, flexible, and interactive communication. Furthermore, psychological factors such as the need for self-expression and social validation, as well as social factors such as environmental influences and digital culture, also influence communication patterns. Furthermore, communication ethics poses a significant challenge in maintaining the quality of interactions in the digital space. Therefore, strengthening digital literacy and communication ethics is necessary to enable Generation Z to manage communication effectively, critically, and responsibly in the digital era.